TOP TEN STRESSORS IN THE HYSTERICAL SUBJECTS OF PESHAWAR - Irfan, Naveed; Badar, Ahmed (Journal of Ayub Medical College Abbottabad, 2002)
Background: Hysteria develops as a reaction to emotional stress or conflict in presence of a series of environmental, biological and personal vulnerability factors or as a part of the current life situation. This study was carried out to determine the top ten stressors in the hysterical subjects of Peshawar. Methods: This study was carried out at Psychiatry department of Khyber teaching Hospital Peshawar Pakistan from January to December 1996. Fifty hysterical subjects satisfying the inclusion and exclusion criteria were selected by convenience sampling. They were interviewed and results were analysed from the entries in a proforma. Results: Stressors were clearly identified in 45 (90%) subjects while in 5 (10%) subjects there were none. The top ten stressors in our population in order of frequency of subjects were '˜disturbed relations with in-laws' (18%), '˜engagement/marriage against wishes' (14%), '˜disturbed relations with spouse' (12%), '˜husband abroad' (10%), '˜conflict with parents' (8%), '˜conflict at work' (8%), '˜failure in exam/study problem' (6%), '˜love problems' (6%), '˜death of spouse' (4%), '˜threat to life (4%). Conclusions: We concluded that stressors were present and identifiable in most of Peshawar hysterics. The pattern of stressors in our subjects was unique to our population and most of these stressors were easily treatable.